KEPUASAN NASABAH DITINJAU DARI KUALITAS PELAYANAN, REPUTASI PERUSAHAAN, DAN PERSEPSI KLAIM NASABAH (STUDI PADA KC AJAB BUMIPUTERA 1912 SURAKARTA) - Yolanda Cahya Utami; Sri Hartono; Eny Kustiyah (ITB AAS INDONESIA Surakarta, 2020)
The purpose of this study is to determine whether there is a significant influence between the variable quality of service, company reputation, and customer claims perception and customer satisfaction. In addition, it is also to find out whether there is a significant simultaneous effect and which variable is the most dominant in influencing customer satisfaction at KC AJB Bumiputera 1912 Surakarta. The method used is a method based on quantitative descriptive, where the sampling technique uses Random Sampling, which is a random sampling technique, regardless of the level contained in the population. The data used are primary data and secondary data with data collection techniques: questionnaires, observations, interviews, and literature study. Data analysis techniques in this study used multiple linear, determination test (R2), F test, and t test. The results of the study can be concluded that: 1) There is an effect of service quality, company reputation, and simultaneous perception of customer claims on customer satisfaction at KC AJB Bumiputera 1912 Surakarta, 2) There is an influence of service quality on customer satisfaction at KC AJB Bumiputera 1912 Surakarta Batik in the City of Solo, 3) There is an influence of company reputation on customer satisfaction in KC AJB Bumiputera 1912 Surakarta, 4) There is an influence of customer perception perceptions of customer satisfaction on KC AJB Bumiputera 1912 Surakarta. Keywords: Service Quality, Company Reputation, Customer Claim Perception, and Customer Satisfaction